Regulation of external labor migration in the Republic of Kazakhstan: problems and opportunities - Syzdykbekov, Ye.S.; Rahmetova, А.М.; Grazhevskaya , N.I. (BUKETOV BUSINESS REVIEW, 2019)
In the article the main issues of state regulation of external labor migration in the Republic of Kazakhstan as well as some issues related to the attraction of foreign labor and illegal labor migration are considered. This research work is aimed to identifying the possible negative effects of uncontrolled attraction of foreign labor for national economy. In the frame of the research an analysis of the dynamics of attracting foreign labor was conducted based on the study of materials of reporting documents of the Ministry of Labor and Social Protection of the Republic of Kazakhstan, as well as statistical data from the Committee on Statistics of the Ministry of National Economy of the Republic of Kazakhstan. Based on the analysis of the materials, problems were identified in the sphere of regulating the attraction of qualified and unskilled foreign labor. The results of the research suggest the need for a more detailed study of the quota tool for labor immigrants in order to protect the domestic labor market, as well as to reduce the number of illegal immigrants. Some recommendations are presented as conclusions.